2017
DOI: 10.1111/1744-7917.12537
|View full text |Cite
|
Sign up to set email alerts
|

The role of herbivore‐ and plant‐related experiences in intraspecific host preference of a relatively specialized parasitoid

Abstract: Parasitoids use odor cues from infested plants and herbivore hosts to locate their hosts. Specialist parasitoids of generalist herbivores are predicted to rely more on herbivore-derived cues than plant-derived cues. Microplitis croceipes (Cresson) (Hymenoptera: Braconidae) is a relatively specialized larval endoparasitoid of Heliothis virescens (F.) (Lepidoptera: Noctuidae), which is a generalist herbivore on several crops including cotton and soybean. Using M. croceipes/H. virescens as a model system, we test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Terpenoids can directly repel herbivores. In cotton, feeding chewing herbivores, including S. exigua and Helicoverpa zea , leads to the release of complex volatile blends, such as β-myrcene, (E)-β-ocimene, DMNT, and (E)-β-caryophyllene, resulting in the increased foraging efficiency of predators and parasitoids [ 41 , 42 ]. In the present work, we showed that silkworm infestation upregulated many genes at the mRNA level in the mevalonate pathway (MVA), such as ACAT (Cluster-8107.10778, L 2 fc = 3.619), HMGCS (Cluster-8107.12939, L 2 fc = 2.634), HMGCR (Cluster-8107.15919, L 2 fc = 4.3524), MVK (Cluster-8107.12465, L 2 fc = 3.146), and FDPS (Cluster-8107.19051, L 2 fc = 3.353) ( Figure 6 B).…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids can directly repel herbivores. In cotton, feeding chewing herbivores, including S. exigua and Helicoverpa zea , leads to the release of complex volatile blends, such as β-myrcene, (E)-β-ocimene, DMNT, and (E)-β-caryophyllene, resulting in the increased foraging efficiency of predators and parasitoids [ 41 , 42 ]. In the present work, we showed that silkworm infestation upregulated many genes at the mRNA level in the mevalonate pathway (MVA), such as ACAT (Cluster-8107.10778, L 2 fc = 3.619), HMGCS (Cluster-8107.12939, L 2 fc = 2.634), HMGCR (Cluster-8107.15919, L 2 fc = 4.3524), MVK (Cluster-8107.12465, L 2 fc = 3.146), and FDPS (Cluster-8107.19051, L 2 fc = 3.353) ( Figure 6 B).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the sex ratio of Hymenopteran is influenced by factors such as diet (Ongaratto et al, 2019), instar (Poncio et al, 2018;Chu et al, 2014), superparasitism (Alvarenga, Dias, Stuhl, & Sivinski, 2015) and size/age of the host (Van Nieuwenhove & Ovruski, 2011;Ueno, 2015). Also, chemical cues are associated with the host characteristics, such as feces (Faraone, Svensson, & Anderbrant, 2017) and its ability to feed on different host plants (Morawo & Fadamiro, 2019). According to the present results, female M. anticarsiae individuals parasitize A. gemmatalis larvae at the end of the first and at the beginning of the second instar; these are the most favorable periods for parasitism for two reasons: larvae attach to the substrate at the end of the first instar and stop feeding, and the larvae stops moving at this point, M. anticarsiae has the advantage in parasitizing immobilized larvae; second reason, larvae remain weak at the beginning of the second instar and are easily exposed to parasitism -parasitoids can take advantage of this weak condition.…”
Section: Sex Ratio and Development Time Of M Anticarsiae Parasitizinmentioning
confidence: 99%
“…Predator–prey interactions lead to adaptations in the behavior of species to optimize foraging and increase the energy efficiency of other vital processes (Hassell & May, 1986; Futuyma & Moreno, 1988; Stiling, 1988; Schenk & Bacher, 2002). Nevertheless, in most cases, studies on higher trophic levels are restricted to insect parasitoids (Vinson, 1976; Morawo & Fadamiro, 2019). This may be due to their oligophagous feeding habit and the necessity to feed on many prey species to complete development (Hassell & May, 1986).…”
Section: Introductionmentioning
confidence: 99%